Considering Refugees Through 100 Years of Geographical Review. Issue 4 (1st October 2019) - Skop, Emily; Tonyan, Joel; Cassiday, Arielle
Abstract : Given the role of the American Geographical Society and its flagship journal, Geographical Review, in the Paris Peace Conference and its prominence in the discipline of geography ever since, this paper considers how the journal takes account of refugees in its pages from 1916 to 2018 using a bibliometric approach. The term "refugee" was tracked in every Geographical Review article published during this time period, using content to generate data and analysis in ivo. First, we identify key trends in scholarship over time, then we note the rise and fall of important key terms, and finally, we examine both the countries analyzed and how these geographies change over time. The results of this bibliometric analysis of refugees in Geographical Review reflect both global geopolitical dynamics and refugee governance structures, and broader trends in epistemology in the discipline of geography. Observations made on these trends and variations indicate a need to further explore shifting paradigms and master narratives, both past and emerging, built around the "refugee" concept and its treatment within the discipline of geography.